Socioeconomic status and exposure to multiple environmental pollutants during pregnancy: evidence for environmental inequity?. Issue 2 (25th October 2010) - Vrijheid, Martine; Martinez, David; Aguilera, Inma; Ballester, Ferran; Basterrechea, Mikel; Esplugues, Ana; Guxens, Monica; Larrañaga, Maribel; Lertxundi, Aitana; Mendez, Michelle; Murcia, Mario; Marina, Loreto Santa; et al.
Abstract : Background: Inequities in the distribution of environmental exposures may add an extra burden to socially disadvantaged populations, especially when acting during vulnerable periods such as pregnancy and early life, but such inequities may be more complex and uncertain than is generally assumed. We therefore examine whether socioeconomic inequities exist in pregnancy exposures to multiple common environmental contaminants in air, water and food. Methods: A Spanish population-based birth cohort study enrolled over 2000 pregnant women between 2004 and 2008. Questionnaires assessed parental education, occupation, country of birth, diet and many other factors. Environmental pollutant assessments included nitrogen dioxide as a marker of traffic-related air pollution, trihalomethanes as a marker of tap water disinfection by-products, organochlorine biomarkers measured in maternal serum during pregnancy (polychlorinated biphenyls (PCB), dichlorodiphenyl dichloroethylene (p, p′-DDE), hexachlorobenzene and β-hexachlorocyclohexane) and mercury concentrations measured in cord blood. Results: Associations between socioeconomic status indicators and nitrogen dioxide and trihalomethanes were generally weak and inconsistent in direction. Concentrations of PCB, hexachlorobenzene and mercury were higher in higher social classes than lower social classes. p, p′-DDE and β-hexachlorocyclohexane were not related to social class. Social class explained between 1% and 5% of the variability in pollutant concentrations, much less than other variables such as region of residence, country of birth and maternal age. Discussion: This study demonstrates that the general assumption that more disadvantaged populations have higher levels of exposure to environmental pollution does not always hold and requires further elucidation in different international settings.